PENGEMBANGAN PETUNJUK PRAKTIKUM PENENTUAN TRAYEK pH DENGAN INDIKATOR ALAMI BERBASIS KEARIFAN LOKAL - Eny Enawaty (Institut Pendidikan Tapanuli Selatan, 2021)
Practical guideline is a facility that can support the success of practicum activities because they can help students prove the truth of a concept. This study aims to: (1) Determine the feasibility of the practicum guideline for determining pH range with natural indicators based on local wisdom of the Singkawang community, (2) Find out the level of student response to the practicum guideline for determining pH range with natural indicators based on local wisdom, (3) Find out the teacher's response to the practicum guideline for determining pH range with natural indicators based on local wisdom of the Singkawang community. This research is a development research with Borg & Gall development model. The practicum guideline developed were validated by media, material, and language experts. The subjects of this research experiment were students of class XI and teachers of SMAN 9 Singkawang and teachers of SMAN 10 Singkawang. The results of the research and development are as follows. (1) The practicum guideline for determining pH range with natural indicators based on local wisdom of the Singkawang community obtained content feasibility of 98.6% (Very High), language feasibility of 95.3% (Very High), and graphic feasibility of 98.6% (Very High), (2) Student responses to the practicum guideline for determining pH range with natural indicators based on local wisdom of the Singkawang community is 77.6% which is a High category, (3) The teacher's response to the practicum guideline for determining pH range with natural indicators based on local wisdom of the Singkawang community is 95.68%, which is Very High category.